Sport magazines are in the system of documentary scientific communication (a report is second) - Свістельник, І. Р. (Physical Education Theory and Methodology, 2012)
The article presents the scientific journals, which form the world of sports documentary evidence. Submitted a list of sports science publications United States, Britain, China, Poland and other countries engaged in providing sports news, sports training, medical and biological problems. It is shown that the results of the study the largest number of scientific publications printed sports in the United States, slightly less than in the UK, Poland and Germany. There are a number of countries that have only one scientific sports magazine. It was determined that scientific journals contribute to the expeditious dissemination of sports information, publish the results of modern research.